Vibration response and fault characteristics analysis of gear based on time-varying mesh stiffness. (June 2020) - Meng, Zong; Shi, Guixia; Wang, Fulin
Highlights: TVMS at different crack and spalling levels is calculated respectively. The influence of different fault evolution levels on dynamic response is studied. The method of signal segmentation by stiffness segmentation is proposed. The sensitivity of statistical indicators to different fault levels is analyzed. Abstract: Gears are prone to failures, which are difficult to detect in the early stage. In this study, the time-varying mesh stiffness of gears teeth with different crack lengths is calculated, and the effects of spalling with different widths, lengths, and locations on the time-varying mesh stiffness of gears are investigated. Considering the time-varying mesh stiffness and sliding friction between teeth, a dynamic gear model with six degrees of freedom is established. Then, the dynamic displacement response of the gear system in the vertical direction is solved by simulation. Due to the difficulty of extracting early fault features, a method of stiffness segmentation is proposed. A short-time Fourier transform is applied to each signal corresponding to the stiffness segment. Changes in the dynamic responses in the time domain, frequency domain, and time–frequency domain with the extension of gear fault are examined. Finally, the trends of various statistical indicators in the time domain and frequency domain with respect to the level of fault extension are compared and analyzed. The results show that the impulse factor is sensitive to fault characteristics.